Reactivity of NK Cells Against Ovarian Cancer Cells Is Maintained in the Presence of Calcium Phosphate Nanoparticles - Hrvat, Antonio; Schmidt, Mathias; Obholzer, Martin; Benders, Sonja; Kollenda, Sebastian; Horn, Peter A.; Epple, Matthias; Brandau, Sven; Mallmann-Gottschalk, Nina (Frontiers in Immunology, 2022)
Calcium phosphate nanoparticles (CaP-NPs) are biodegradable carriers that can be functionalized with biologically active molecules. As such, they are potential candidates for delivery of therapeutic molecules in cancer therapies. In this context, it is important to explore whether CaP-NPs impair the natural or therapy-induced immune cell activity against cancer cells. Therefore, in this study, we have investigated the effects of different CaP-NPs on the anti-tumor activity of natural killer (NK) cells using different ovarian cancer (OC) cell line models. We explored these interactions in coculture systems consisting of NK cells, OC cells, CaP-NPs, and therapeutic Cetuximab antibodies (anti-EGFR, ADCC-inducing antibody). Our experiments revealed that aggregated CaP-NPs can serve as artificial targets, which activate NK cell degranulation and impair ADCC directed against tumor targets. However, when CaP-NPs were properly dissolved by sonication, they did not cause substantial activation. CaP-NPs with SiO2-SH-shell induced some activation of NK cells that was not observed with polyethyleneimine-coated CaP-NPs. Addition of CaP-NPs to NK killing assays did not impair conjugation of NK with OC and subsequent tumor cytolytic NK degranulation. Therapeutic antibody coupled to functionalized CaP-NPs maintained substantial levels of antibody-dependent cellular cytotoxic activity. Our study provides a cell biological basis for the application of functionalized CaP-NPs in immunologic anti-cancer therapies.